Evaluation of Development in Zakat Literature - Aliyu Olugbenga Yusuf; Bello Yerima; Grace Ape (International Journal of Zakat, 2020)
The study adopted the Scientometrics analysis to evaluate the development in zakat scholarly publications. Scholarly publications on zakat were gathered using the Scopus online databases and later analysed using Microsoft Excel software. The study helps analyse, evaluate and feature scholarly publications based on some considered performance indicators. The study discovered varied trend in the citation of literature based on authorship (single and multiple) and also published date. Zakat authors and researcher cut across several fields and disciples. More publications are discovered in Asian regions and less funding or sponsorship for zakat research is observed.